Escalonamento de nanocompósito de UHMWPE contendo rGO : contribuição ao mapeamento e otimização de etapas experimentais - Ana Flávia Tavares Soares Pereira (2023)
This work presents the mapping and experimental execution of the masterbatch production scaling process to obtain an ultra-high molecular weight polyethylene (UHMWPE) nanocomposite containing reduced graphene oxide (rGO), aiming pilot-scale production. The master's work investigates the evolution of the production in an increased scale of the starting load, the exfoliation parameters of the load, the most adequate concentration of the masterbatch (MB) and evaluation of the properties of the nanocomposite of UHMWPE/rGO in the concentrations of 0.10 and 0.25 wt.% of rGO in the laboratory, and subsequently, production of 120 kg of nanocomposites on a pilot scale in an industrial environment. For all stages, validations were carried out through relevant characterization techniques and analysis of structural and fundamental properties, guaranteeing the quality and performance of the nanocomposite comparing with the results obtained in the laboratory. 10 kg of masterbatch containing 3 wt.% of nanofiller (MB3%) were produced in the CTNano infrastructure, which resulted in 30 kg of UHMWPE/rGO nanocomposite containing 0.1 wt.% and 90 kg of nanocomposite with 0.25 wt.% of rGO. The conformation of the materials was carried out in an industrial environment on a pilot scale. The characterization of the nanocomposites on a pilot scale was carried out for different regions of the plate, in order to verify the possible influences of the processing on the product. It was observed that the nanofiller positively influenced the processing of the material in a piston extruder (RAM), contributing to homogenization of the heat treatment in the matrix, which led to a more adequate conformation, with gains in properties. The best results were observed for the nanocomposite containing 0.25 wt.% of rGO. In relation to the pure polymer, UHMWPE/rGO (0.25%) showed superior results in 16% in crystallinity, 48% in elastic modulus, 26% in impact resistance, 48% in hardness, 9% and 24% in abrasive resistance to two- and three-body, respectively, and 10% increase in contact angle.